Karakterisasi Penampilan Agronomi Beberapa Aksesi Bawang Merah (Allium cepa L) di Dataran Rendah Karawang - Falah, Ridhwan; Azizah, Elia; Syafi’i, Muhammad (Faculty of Agriculture Universitas Singaperbangsa Karawang, 2023)
The demand for onions in Indonesia is always increasing, but shallot production has not been able to meet the needs of the community. The purpose of this study was to obtain the best accessions that can be used in the selection of plant breeding that has the best potential in the Karawang area. So that it can increase the productivity and resistance of shallot plants in the lowlands of Karawang. The onion research was carried out for 3 months, starting from December 2021 to March 2022. Located in UNSIKA New Land, Pasir Jengkol Village, Majalaya District, Karawang Regency, West Java Province. The location of the coordinates is 6ᵒ18'5